Electrical characteristics of dielectric barrier discharge / Tay Wee Horng - Tay, Wee Horng (2013)
The industrial application of the dielectric barrier discharge (DBD) has a long tradition. However, the lack of understanding of some of its fundamental issues, such as the stochastic behaviors, is still a challenge for DBD researchers. In this project, considerable efforts to understand the fundamental aspects of DBD have been made. The aim of this work is to study the electrical characteristics of DBD to determine a suitable condition for utilization of the device for applications. Several diagnostic tools such as high-voltage probe, resistive current, charge measurement, and high-speed camera imaging were employed for the investigation. In order to study the electrical behaviors of DBD, the experimental work was carried out in two parts: current pulse amplitude statistical studies and the energy investigation. For the pulse amplitude statistical studies, the stochastic variation of the current pulse amplitude has been analyzed by the statistical method. The stochastic behavior of the discharge current amplitude has been compared with a proposed empirical equation of the distribution pulse height. This proposed statistical function is found to be in good agreement with the experimental discharge pulse amplitude variation for discharges with varying space gaps. This empirical equation successfully predicts the existence of two discharge regimes, which were observed from the experimental results. For the energy investigation, the DBD dissipation energy was studied experimentally and numerically. A dynamic circuit model constructed with Matlab Simulink accurately simulated the discharge energy of DBD. The surface resistance introduced in this electrical model represents the average effect that effectively accounts for the resistance encountered by the charges between the discharging and non-discharging regions on the dielectric. The expanded QV Lissajous can be reasonably explained by the fact that the total energy is summed by the energy of the DBD discharge and the energy consumed by the spreading II charges on the dielectric surface. By having the experimental results accurately fitted with the simulated results from the model, the efficiency of discharge can be obtained from the electrical modeling. The efficiency of the DBD has been found to be higher with a smooth surface compared to a rough surface. The efficiency is reduced when the applied voltage is increased. Based on the energy and current pulse amplitude distribution model, the DBD system can be designed according to the desired condition by controlling the required energy efficiency and pulse height distribution.